A Mixed H2/H∞ Control Method for UAV Based on T-S Fuzzy Model - SUN Miaoping; DING Nan; NIAN Xiaohong (Kongzhi Yu Xinxi Jishu)
A mixed H2/H∞ control strategy was proposed in this paper to achieve a stable tracking trajectory of the UAV(unmanned aerial vehicle). Firstly, the quadrotor UAV was divided into three subsystems: the altitude, the position and the attitude. By selecting the appropriate premise variables, three T-S fuzzy error models were established. Then the uncertain terms such as lift coefficient, drag coefficient and moments of inertia were described by interval matrix. In order to ensure the UAV can fly stably under the influence of external disturbances such as breezes, a mixed H2/H∞ controller with D stability constraints were designed based on the linear matrix inequality method and pole placement theory. Finally, simulation results of a quadrotor UAV show the effectiveness of the proposed control strategy.